RESPON SISWA TERHADAP PEMBELAJARAN DARING DALAM PENDIDIKAN JASMANI MASA PANDEMI COVID-19 - Rasidi Rasidi; Andika Triansyah; Eka Supriatna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the responses of grade VIII students to onlinelearning in physical education during the Covid-19 pandemic at SMPN 16Pontianak in 2021. This research is a quantitative descriptive survey method.Data collection techniques used questionnaires and data analysis techniquesused percentage descriptive statistics. The population numbered 277 students,class VIII SMPN 16 Pontianak using saturated sample techniques. Results ofresearch on the responses of class VIII students to online learning in physicaleducation during the Covid-19 pandemic at SMPN 16 Pontianak in 2021,category strongly agree 4.17% or 4 students, 12.5% or 12 students agreecategory, 77.08% or 74 students disagree, and 6.25% or 6 students stronglydisagree.this result means that the response of grade VIII students to onlinelearning in physical education during the Covid-19 pandemic at SMPN 16pontianak in 2021 expressed disagreement.Keywords : response, online learning, physical education, students